HUBUNGAN ANTARA PENGUASAAN KOSAKATA DENGAN KEMAMPUAN MENYIMAK BAHASA JERMAN SISWA KELAS XI BAHASA - Selviana, Yulia; Mannahali, Misnah; Dalle, Ambo (Universitas Negeri Makassar, 2020)
Abstract. Correlation between Vocabulary Mastery with listening ability in German language Class XI students SMAN 13 Bone. Thesis. Faculty of Languages and Literature. State University of Makassar.This study aims to obtain data and information about the relationship between vocabulary mastery and te ability to listen to German in class XI language at SMA 13 Bone.This research is descriptive research.The population of this study was all studens of class XI Languages totaling one Class with 28 students. The sample of this study was 28 students of class XI language selected through total sampling techniques.Research data was collected through a written test, and analyzed using product moment correlation.The results of this study indicate that there is a significant link between mastery of vocabulary with the listening ability of German language class XI student SMA Negeri 13 Bone Rh = (0.574) >Rt = (0.374) with a significant level of 5%.